Uneasy virtue - Driver, Julia, 1961- (Cambridge studies in philosophy., 2001)
"The predominant view of moral virtue can be traced back to Aristotle. He believed that moral virtue must involve intellectual excellence. To have moral virtue, one must have practical wisdom - the ability to deliberate well and to see what is morally relevant in a given context. Julia Driver challenges this classical theory of virtue, arguing that it fails to take into account virtues that do seem to involve ignorance or epistemic defect. Some "virtues of ignorance" are counterexamples to accounts of virtue that told that moral virtue must involve practical wisdom. Modesty, for example, is centrally considered to be a virtue even though the modest person may be making an inaccurate assessment of his or her accomplishments." "Driver argues that we should abandon the highly intellectualist view of virtue and instead adopt a consequenialist perspective that holds that virtue is simply a character trait that systematically produces good consequences. In this approach, what counts as human excellence will be determined by conditions external to agency, such as consequences. Uneasy Virtue presents a stimulating and accessible defense of the idea that the importance of the virtues and the ideas of virtue ethicists are best understood within a consequentialist framework."--Jacket